Analysis of the Impact of the 2024 East Java Gubernatorial Election on the Income of Screen Printing MSMEs in Grati District, Pasuruan Regency - Indarti, Nunuk; In, Churin; Sobakh, Nurus; Aufin, Muhammad (IJBLE Scientific Publications Community Inc., 2025)
The five-year gubernatorial election is a highly anticipated event for MSMEs that provide visual attributes, as gubernatorial candidates and their campaign teams undertake numerous activities to ensure a smooth campaign. Grati District in Pasuruan Regency is one of the areas with a relatively high concentration of screen-printing MSMEs, both in terms of business activity and their contribution to the local creative economy. This study uses a quantitative approach because its main objective is to analyze the relationship between variables X and Y through numerical measurements and statistical data processing. The subjects of this study were 10 screen printing MSMEs operating before, during, and after the 2024 East Java gubernatorial election. Based on the results of the T test, it can be seen that thitung The variable of the Gubernatorial Election (X) is 4.755 with a significance level of a = 0.05. At the same time, the table above shows a significance of 0.000, so the regression coefficient result is 0.000 < alpha 0.05. Thus, it can be concluded that there is an influence of the 2024 East Java Gubernatorial Election Activities on the income of MSMEs in the Screen Printing Services Sector in Grati District, Pasuruan Regency.